The Ability to Produce Description Texts for Class VII Students of Mts Al-Qalam, Jereweh District - Abd Hamid MK; Burhanuddin Burhanuddin; Saharuddin Saharuddin (International Journal of Social Service and Research, 2022)
This study aims to determine the ability to produce descriptive text of class VII students of MTs Al-Qalam, Jereweh District, by paying attention to aspects of descriptive text content, descriptive text structure, and linguistic characteristics of descriptive text. The method used in this research is descriptive quantitative. The data collection technique used is an ability test in the form of a written test. The population in this study were all 7th grade students of MTs Al-Qalam, Jereweh District in the 2021/2022 academic year, totaling 13 students, consisting of 9 boys and 3 girls. Jereweh saw from the aspects assessed, that students have not been able to write a descriptive text. This is evidenced by the results of student work which shows that students who get a score of 90 are 1 person and those who get a score of 70 are 2 people, who get a score of 65 as much as 3 people, who get a score of 60 as much as 5 people, who get a score of 55 as much as 2 people. The conclusion is that the ability to produce texts for class VII students of MTs Al-Qalam, Jereweh District for the 2021/2022 academic year, totaling 13 has not been able to be as mandated by the 2013 Curriculum.